Observational connection of non-thermal X-ray emission from pulsars with their timing properties and thermal emission. Issue 3 (6th February 2023) - Chang, Hsiang-Kuang; Hsiang, Jr-Yue; Chu, Che-Yen; Chung, Yun-Hsin; Su, Tze-Hsiang; Lin, Tzu-Hsuan; Huang, Chien-You
ABSTRACT: The origin and radiation mechanisms of high-energy emissions from pulsars have remained mysterious since their discovery. Here we report, based on a sample of 68 pulsars, observational connection of non-thermal X-ray emissions from pulsars with their timing properties and thermal emissions, which may provide some constraints on theoretical modeling. Besides strong correlations with the spin-down power E and the magnetic field strength at the light cylinder B lc, the non-thermal X-ray luminosity in 0.5–8 keV, L p, represented by the power-law component in the spectral model, is found to be strongly correlated with the highest possible electric field strength in the polar gap, E pc, of the pulsar. The spectral power index Γ p of that power-law component is also found, for the first time in the literature, to strongly correlate with E, B lc, and E pc, thanks to the large sample. In addition, we found that L p can be well described by L p ∝ T 5.96 ± 0.64 R 2.24 ± 0.18, where T and R are the surface temperature and the emitting-region radius of the surface thermal emission, represented by the blackbody component in the spectral model. Γ p, on the other hand, can be well described only when timing variables are included and the relation is Γ _p= (T^-5.8± 1.93R^-2.29± 0.85P^-1.19± 0.88P^0.94± 0.44) plus a constant. These relations strongly suggest the existence of connections between surface thermal emission and electron–positron pair production in pulsar magnetospheres.